2012
DOI: 10.5586/asbp.2012.017
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the pollen morphology of traditional cultivars of Prunus species in Sicily

Abstract: In this study pollen grains of 13 cultivars and 3 rootstocks belonging to 5 species (P. armeniaca, P. domestica, P. dulcis, P. persica, P. avium) of the genus Prunus collected from North-East Sicily were examined for the micromorphological characterization through the scanning electron microscopy (SEM). The length of polar axis (P) and the equatorial diameter (E) of grain, P/E ratio, the length of colpi (C), diameter of perforations (DP) and the number of perforations in 25 µm 2 (PN), the width of muri (WM), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
4
5
0
Order By: Relevance
“…The morphological characters of pollen from genera Prunus and Pyrus showed a prolatespheroidal shape class. A similar pollen shape class was observed by Fogle (1977) and Geraci et al (2012). A prolate shape was observed by Chwil (2015) Zuraw et al (2015), who had found that Rosa pollen size ranged from 29.2-34.2 µm in polar and 29.4-33.5 in equatorial view, tricolporate aperture and striate exine.…”
Section: Discussionsupporting
confidence: 79%
“…The morphological characters of pollen from genera Prunus and Pyrus showed a prolatespheroidal shape class. A similar pollen shape class was observed by Fogle (1977) and Geraci et al (2012). A prolate shape was observed by Chwil (2015) Zuraw et al (2015), who had found that Rosa pollen size ranged from 29.2-34.2 µm in polar and 29.4-33.5 in equatorial view, tricolporate aperture and striate exine.…”
Section: Discussionsupporting
confidence: 79%
“…Flowers and inflorescences have important taxonomic value, and their developmental process contains abundant information for systematics and evolutionary studies (Endress 2011). Previous studies on Prunus have focused on its anatomy (Sterling 1953a(Sterling , b, 1964Haskell and Dow 1955;Endress and Stumpf 1991;Zhang 1992;Chin et al 2013), palynology (Hebda et al 1991;Geraci et al 2012;Shi et al 2013), paleontology (DeVore andPigg 2007;Benedict et al 2011;Li et al 2011), phylogenetics, and phylogeography (Bortiri et al 2002;Wen et al 2008;Chin et al 2010Chin et al , 2014Liu et al 2013;Zhao et al 2016). Evans and Dickinson (1999a) compared the inflorescence and floral development of P. virginiana (subg.…”
Section: ;mentioning
confidence: 99%
“…The subfamily Dryadoideae has been studied by Hebda et al (1988b) and Beug (2004). The pollen of the subfamily Spiraeoideae has been studied by Huang (1972), Hebda et al (1988aHebda et al ( , 1988b, Jones et al (1995), Wang et al (1995), Beug (2004), Bednorz et al (2005), Dönmez (2008), Joneghani (2008), Sorkheh et al (2008), Vafadar et al (2010), Zamani et al (2010), Li et al (2011a), Miyoshi et al (2011), Geraci et al (2012, Ćalić et al (2013), Shi et al (2013) and Perveen and Qaiser (2014). Based on these studies, the Rosaceae pollen grains from Lavanttal can be affiliated with Prunus.…”
mentioning
confidence: 99%